Human-Centered Artificial Intelligence Model in Classroom Management in Early Childhood Islamic Education Study Programs - Idris, Meity H.; Riza, Eva; Manfaatin, Eva; Chai, Som; Akhtar, Shazia (STAI Publisistik Thawalib Jakarta, 2026)
Digital transformation demands adaptive classroom management; however, the implementation of Artificial Intelligence in Islamic higher education has not yet been structured into a human-centered model that considers pedagogical, ethical, and humanistic values. This study aims to analyze the needs of digital classroom management and to formulate a contextual Human-Centered Artificial Intelligence model for Islamic higher education. The research employed a qualitative approach with conceptual development studies through interviews, classroom observations, academic documentation, and interpretive thematic data analysis. The findings suggest that classroom management is confronted with difficulties stemming from diverse student capabilities, fluctuations in learning engagement, and inadequate utilization of learning data. To mitigate these issues, a Human-Centered Artificial Intelligence Model was developed, incorporating learning analytics, adaptive recommendation systems, and humanistic pedagogical tenets grounded in Islamic educational principles. This model designates educators as the principal decision-makers, with AI functioning as a data-driven support system. The model's implementation could potentially augment learning efficacy, personalize the learning experience, and sustainably enhance the quality of pedagogical interactions. Consequently, the integration of Human-Centered Artificial Intelligence fortifies adaptive classroom management by harmonizing technology, humanistic values, and the strategic function of educators. This study offers a conceptual model of AI-driven classroom management that is humanistic, contextually relevant, and pertinent to Islamic higher education within the digital age.